Culture, individualization and violence in “heavy music” in the city of Lima (1994-2014) - Yépez Aguirre, Jimmy (2017)
This study was aimed at identifying the benefits that have the qualitative method of grounded theory on the different aspects of feeling and thinking of the metaleros of Lima in order to analyze their gregarious relations in society. In this regard the following objectives: Understand that reproduces the individualization of social life, cultural commodification and fetishization of music, the feelings and thoughts of the metalheads of Lima. Use of depth interview which was applied to a nonrandom sample of 30 youth and adults metalheads (14 to 48 years as age ranges or limits). The Rockandad and Metaldad, which serve to give the interpretation to the issues raised: two conceptual categories identified. And finally a conceptual theoretical instrument called pyramidal dialectic was prepared to give way to explaining the research.